MXene-Ti3C2Tx-Based Neuromorphic Computing: Physical Mechanisms, Performance Enhancement, and Cutting-Edge Computing - Kaiyang Wang; Shuhui Ren; Yunfang Jia; Xiaobing Yan; Lizhen Wang; Yubo Fan (Nano-Micro Letters)
Highlights This review reveals the advantages of MXene-Ti3C2Tx for neuromorphic devices, classifies the core physical mechanisms, and outlines strategies to drive targeted optimization and future innovation. The review outlines three key engineering strategies: doping engineering, interfacial engineering, and structural engineering, while also providing comprehensive guidance for material and device improvement. MXene-Ti3C2Tx-based devices demonstrate groundbreaking potential in next-generation computing, such as near-sensor computing and in-sensor computing, enabling faster and more energy-efficient data processing directly at the sensor level.